2010
DOI: 10.1111/j.1468-3083.2009.03424.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory study of rosacea in northern Greece

Abstract: Our results suggest the pivotal role of chronic sun exposure in the pathogenesis of rosacea. Demodex folliculorum represents a significant cofactor that may contribute to the transition of the disease from a vascular to an inflammatory stage. The low positive results of direct and indirect immunofluorescence do not support a potential autoimmune role in the development of rosacea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 35 publications
9
60
1
3
Order By: Relevance
“…Generally ETR is the most common, followed by PPR, in a 4:1 ratio [1,3,22]. However, a predominance of PPR was reported in previous studies of subjects with darker skin type [23,24]. A rosacea patient may have more than one overlapping subtype simultaneously, an overlap permitted by the NRS system [13,15,17,25].…”
Section: Discussionmentioning
confidence: 98%
“…Generally ETR is the most common, followed by PPR, in a 4:1 ratio [1,3,22]. However, a predominance of PPR was reported in previous studies of subjects with darker skin type [23,24]. A rosacea patient may have more than one overlapping subtype simultaneously, an overlap permitted by the NRS system [13,15,17,25].…”
Section: Discussionmentioning
confidence: 98%
“…The predominance of ETR over PPR and of female sex, and the peak age range distribution in this study concur with results of previous investigations in subjects with lighter phototypes. 13,15,18 However, studies in subjects with darker phototypes 16,17 revealed a predominance of PPR. This disparity may be due to the intrinsic difficulty in visually detecting erythema in dark skin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the level of antinuclear antibodies in RS patients was broadly studied. One article from 2010 highlighted ANA in 21,1% of the patients diagnosed with RS and the authors ruled out autoimmunity involvement in RS development in the studied lot (46). In another work, as much as 53,5% of the RS patients included in the research had ANA titer higher than 1:160 (13,86% above 1:320, 8,9% above 1:640, 6,93% above 1:1280).…”
Section: Results Resultsmentioning
confidence: 97%